Integrations between Exchange Rates and Stock Market Before and After the 2007 Financial Crisis: Empirical Evidence from Kazakhstan Financial Market - Ramazanov, Sherif (2010)
This study examines the long-run and short-run interrelations between Kazakhstan stock market and four major currencies: US Dollar, Euro, Chinese Yuan and Russian Ruble. The study determines causality relationship between stock market and each of the exchange rates for the period from July 2000 till June 2010. To understand the impact of the 2007 financial crisis the data sample of ten years was divided into three sub periods: pre crisis (July 2000-May 2007), crisis (June 2007 – September 2007) and post crisis (September 2007-June 2010). By applying bivariate and multivariate cointegration tests the paper shows existence of long-run relationship between them. However, short-run cointegration test illustrates that Euro and Rubles are more cointegrated with Kazakhstan stock market than other two exchange rates. Furthermore, causality test shows that the time of instability has strong effect on the relationship between stock market and exchange rates and it tends to increase causality relationships between variables. The results of this study are consistent with previous studies that proved that crisis has a temporary effect on relationship between stock market and exchange rate. Moreover, the research shows that exchange rates fluctuation could be one of the signals that government could use in order to keep control over financial stability of a country and potential investor or analysts could employ to predict future fluctuations of a particular stock market.